Uji Daya Hambat Antibakteri Kombinasi Ekstrak Kulit Buah Manggis Komersial (Garcinia mangostana L) dan Amoksisilin Terhadap Bakteri Methicillin Resistant Staphylococcus aureus (MRSA) - Permana, Atna; N, Mazlan (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Amoxicillin is a beta-lactam antibiotic compound and has the chemical name alpha-amino-hydroxylbenzyl-penicillin. This drug was initially developed to have an advantage over ampicillin: it can be better absorbed in the digestive tract. The chemical contents of mangosteen rind (KBM) are xanthone, mangostin, garcinone, flavonoids and tannins. In addition, mangostenol, mangostenone A, mangostenone B, trapezifolixanton, tovofilin B, alpha mangostin, beta mangostin, garsinone B, mangostinone, epicatechin, and mangostanol. Mangosteen (Garcinia Mangostana L.) has many pharmacological properties; KBM also has antimicroorganism properties. It is estimated that alpha mangostin and/or KBM extract works in a similar way to amoxicillin, namely stopping the formation of bacterial cell walls. Alpha mangostin (flavonoid) or KBM extract (clavulanic acid) have similar groups or active substances. The aim of this research is to prove the antibacterial mechanism of action of the combination of KBM (Garcinia mangostana L) extract with amoxicillin on the growth of MRSA bacterial cells. Conclusion: The MIC of commercial GML extract, amoxicillin against MRSA is 137.50 µg/mL and 250.00 µg/mL respectively. The checkerboard test showed synergistic activity of commercial GML (34.38 µg/mL) plus amoxicillin (62.50 µg/mL) against Methicillin-Resistant Staphylococcus aureus (MRSA) or Staphylococcus aureus ATCC BAA-3. The FIC index of amoxicillin plus GML against MRSA strains was 0.50. The synergistic activity of this combination was confirmed by a 2 log10 CFU/mL reduction of these treated cells compared with amoxicillin treatment alone. Conclusion that the combination of commercial mangosteen peel extract and amoxicillin is able to inhibit the growth of Methicillin-Resistant Staphylococcus aureus (MRSA). Key words: Alpha mangostin, amoxicillin, Staphylococcus aureus, FIC